A dynamic approach to inflation targeting in transition economies - Lucjan T. Orlowski (Rheinische Friedrich-Wilhelms-Universität Bonn, Zentrum für Europäische Integrationsforschung (ZEI), 2000)
This study views inflation targeting as a viable monetary regime for more advanced transition economies. A dynamic approach to the trajectory of disinflation and to the flexibility of direct inflation targeting is presented in the context of achieving monetary convergence to the EU/AMU. The candidate countries are advised to begin from strict inflation targeting and to follow with a more flexible inflation targeting regime before they establish a necessary `foundational credibility' and monetary stability. These steps, ultimately followed by a euro-peg, are necessary in preparing for accession to the eurozone. The early experiences of the Czech Republic and Poland with inflation targeting are examined.
Keywords: E32; E52; P33; 330; Inflation Targeting; Währungspolitik; Übergangswirtschaft; Wirtschaftliche Anpassung; EU-Erweiterung; Ts